Pengaruh Model Pare (Preview, Ask, Read, Evaluate) Terhadap Kemampuan Berpikir Tingkat Tinggi Siswa SD Inpres Galangan Kapal IV Kecamatan Tallo Kota Makassar - Nurhaedah Nurhaedah; Abdul Rahman; Nursiah Nursiah; Nur Abidah Idrus (Universitas Negeri Makassar, 2021)
This study aims to describe the high-level thinking skills of students of SD Inpres Galangan Kapal IV, Kecamatan Tallo Kota, Makassar and to determine whether there is influence of the PARE learning model (preview, ask, read and evaluate) on high-level thinking skills of SD Inpres Galangan Kapal IV Kecamatan Tallo Kota, Makassar. This study uses a quantitative approach to the type of experimental research. The research design used was pre-experiment with the form of intag group comparison. The population in this study were all students of SD Inpres Galangan Kapal IV Kecamatan Tallo Kota, Makassar. The sample in this study were fifth grade students who were divided into two groups, namely the experimental group and the control group using the purposive sampling technique. Data collection techniques used in this study are observation and documentation. The data analysis technique used is descriptive analysis and inferential analysis using the independent sample t-test. The results of this study indicate that the higher order thinking skills of students in the experimental group were in the moderate category, while those in the control group were in very low categories. The results of the Independent Sample T-Test, post-non-test scores in the experimental group and the control group showed the results of Sig. (2-tailed) <0.05, which means that there is the influence of the PARE learning model (preview, ask, read and evaluate) on the higher order thinking skills of students of SD Inpres Galangan Kapal IV Kecamatan Tallo Kota Makassar. Based on the results of this study it can be concluded that the PARE learning model (preview, ask, read and evaluate) can affect students' high-level thinking skills.